Exercise capacity after long-term physical activity on prescription provided by physiotherapists - Daniel Karsberg Zotterman; Åsa Cider; Stefan Lundqvist (Scandinavian Journal of Primary Health Care)
Background: Research has shown that physical activity on prescription (PAP), used in Swedish healthcare, increases patients’ physical activity, but data are lacking regarding the long-term effects of PAP on exercise capacity. Therefor exercise capacity was evaluated in patients with metabolic risk factors, after 4.5 years of PAP treatment provided by physiotherapists in primary healthcare.Method: This study included 98 patients (49% women; mean age, 56 years) with metabolic risk factors, who were still physically inactive after a previous 6-month PAP treatment. The patients received physiotherapist-provided PAP treatment for 4.5 years, including 11 follow-ups and 6 exercise capacity tests.Results: After 4.5 years, 41 patients completed the final exercise capacity test (58% drop-out rate). Compared to baseline, the whole cohort exhibited a significantly increased exercise capacity (9.1 W, p = 0.014) with a small effect size (r = 0.27), with no significant differences associated with age or gender.Conclusion: The increased exercise capacity may indicate positive effects on longevity, and consolidates previous findings that long-term behavior change is possible among physically inactive patients. It also demonstrates the feasibility of continuous exercise capacity testing with physiotherapist support in an ordinary primary care setting. The drop-out rate and lack of control group complicate the interpretation of the effects of PAP treatment on the increased exercise capacity. Further research should strive for an RCT study design.